Teaching in the Middle Grades Today: Examining Teachers’ Beliefs About Middle Grades Teaching - Mike DiCicco; Chris M. Cook; Shawn A. Faulkner (Middle Grades Review, 2016)
Since the beginning of the middle school movement in the mid-1960s, middle level advocates have called for a school experience for young adolescents grounded in adolescent development that engages students in meaningful learning (Eichhorn, 1966; Alexander & Williams, 1965). The aim of this exploratory multi-case study was to understand middle level teachers’ beliefs about middle level instruction in the current educational environment. To gain this understanding, researchers asked ten current middle grades teachers with varying levels of experience to discuss their beliefs regarding their primary purpose as a middle grades teacher, the current status of middle level teaching, their best and worst instructional lessons, and their perceived barriers to teaching at the middle level. The teachers described the role of teaching in the middle grades as challenging and stressful, but of great importance. In general, they described instruction that included discovery, student engagement, and relevance in an effort to address students’ academic development. There was minimal mention of the non-academic aspects of adolescent development. Finally, teachers viewed curriculum restrictions, students’ attitudes toward learning, difficulty with differentiation, and lack of technology as significant barriers to their success in the classroom.
Keywords: middle grades; teaching